Socialization of Land Use by Applying Modern Agriculture with Hydroponic Cultivation - Surya Fajri; Azwar Annas Manurung; Lokot Ridwan Batubara; M. Rizky Marpaung (Pusat Publikasi Nusantara, 2023)
Community service is an activity that realizes and improves the quality of community knowledge in helping the problems experienced by the community in the community. Through the Thematic Real Work Lecture (KKNT) program based on community service, this activity is to increase students' sense of solidarity with the existing conditions of the community. The use of land with hydroponic cultivation is an alternative that can be done by utilizing minimal yard land and being able to use used goods. Farming with hydroponics is very environmentally friendly in addition to not using pesticides, also the production can be used alone or as an economic source of household income. In addition, the outputs obtainedare n: (1) Improvement of superior quality of resources; (2) improving household economic resources; (3) Encourage the progress of the village. On the other hand, to ensure the discipline and participation of KKNT student participants and the community, by seeing the success in the form of outputs produced